Effects of substitution of Ti4+ by Nb5+ on the electrical properties of BaTi2O5 prepared by a floating zone method. Issue 15 (15th November 2016) - Shiga, Keiji; Katsui, Hirokazu; Kakuda, Hiroyuki; Yoshikawa, Kazuma; Tsuneyoshi, Jun; Goto, Takashi
Abstract: Nb 5+ -substituted single-crystalline BaTi2 O5 (Ba(Ti1− x Nb x )2 O5+ z ) was synthesised by a floating zone method, and the effect of Nb 5+ substitution on the dielectric properties of Ba(Ti1− x Nb x )2 O5+ z was investigated. The growth direction of Ba(Ti1− x Nb x )2 O5+ z was parallel to the b axis. The a lattice constant and β angle increased from 1.6906 to 1.6918 nm and from 103.09° to 103.13° at x =0–0.7 at%, respectively. With increasing x, the Curie temperature of Ba(Ti1− x Nb x )2 O5+ z decreased from 750 to 652 K. A complex impedance plane plot of BaTi2 O5 at 598 K in the b direction showed a semicircle at high frequencies and a spike inclined at 45° to the real axis at low frequencies, indicating ionic conduction of bulk BaTi2 O5 . At x >0.002 (0.2 at%), the complex impedance plots of Ba(Ti1− x Nb x )2 O5+ z showed no inclined spike, suggesting dominantly electronic conduction. The electrical conductivity of Ba(Ti1− x Nb x )2 O5+ z increased with temperature with an activation energy of 1.4 to 1.7 eV and was minimum at x =0.001 (0.1 at%). The spontaneous polarisation of Ba(Ti0.998 Nb0.002 )2 O5+ z was 2.7×10 −2  C m − 2, which was 2.5 times higher than that of BaTi2 O5 .